Fossil frenzy - Dixon, Franklin W. (Dixon, Franklin W. Hardy boys secret files, 2014)
"A missing dinosaur tooth makes for a massive investigation in this Hardy Brothers Secret Files Mystery. Frank and Joe are excited for their field trip to the Bayport Museum of Natural History with their science club. Not only will they get to see some awesome dinosaur skeletons on display, but they also get to go on their very own fossil dig on the museum grounds. At the dig, fellow classmate Tico uncovers an old dinosaur tooth--even though Tico's biggest competition in the club, Aisha, claims she found it first. And when Tico realizes his tooth is missing--a tooth that turns out to be immensely valuable--all signs point to Aisha. But is she really the culprit? It's up to Frank and Joe to dig deep for the answers in a case that is bigger than they ever imagined!" --